UPAYA GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) SISWA KELAS VIII DI SMP NEGERI 4 MAPAT TUNGGUL - Hajar, Benti; Syafrizal, Syafrizal (Cahaya Ilmu Bangsa Institute, 2024)
This article aims to analyze the efforts of teachers in increasing motivation to learn Islamic religious education for students. The research setting took place at SMP Negeri 4 Mapat Tunggul, to be precise in class VIII students. The focus of this research, apart from discussing teacher efforts in increasing student learning motivation, is also aimed at analyzing various obstacles or obstacles experienced by students while participating in the learning process of Islamic religious education. This study used a qualitative approach with an analytical descriptive study method. Research data collection instruments using interview and observation techniques. Then the data were analyzed through data reduction techniques, data presentation, and data verification. The results of this study concluded that the efforts of Islamic religious education (PAI) teachers in increasing student learning motivation in PAI subjects in grade VIII of SMP Negeri 4 Mapat Tunggul were quite good, this can be seen from the various efforts made by the teacher, such as: using the Lecture Method, Questions and Answers and Discussion when teaching Islamic religious education learning. Then, giving assignments to students individually, giving praise (appreciation) to students who answer questions correctly, and giving value to each Islamic religious education learning exercise. The obstacle faced by the teacher was the unpreparedness of the students in accepting the subject matter, and there were some students who paid less attention to the learning material when the teacher explained the material, and there were also those who slept during the lesson. Efforts made by the teacher in overcoming these problems are by activating the classroom atmosphere through giving assignments and direct questions about Islamic religious education learning materials. Artikel ini bertujuan untuk menganalisa upaya guru dalam meningkatkan motivasi belajar pendidikan agama Islam bagi siswa. Latar penelitian bertempat di SMP Negeri 4 Mapat Tunggul, tepatnya pada siswa kelas VIII. Fokus penelitian ini selain membahas upaya guru dalam meningkatkan motivasi belajar siswa, juga ditujukan untuk menganalisa berbagai kendala atau hambatan yang dialami siswa selama mengikuti proses pembelajaran pendidikan agama Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi deskriptif analitis. Instrumen pengumpulan data penelitian menggunakan teknik wawancara dan observasi. Kemudian data dianalisis melalui teknik reduksi data, penyajian data, dan verifikasi data. Hasil penelitian ini menyimpulkan bahwa upaya guru Pendidikan Agama Islam (PAI) dalam meningkatkan motivasi belajar siswa pada mata pelajaran PAI kelas VIII SMP Negeri 4 Mapat Tunggul cukup baik, hal ini dilihat dari berbagai upaya yang dilakukan guru, seperti: menggunakan Metode Ceramah, Tanya Jawab dan Diskusi saat mengajar pembelajaran pendidikan agama Islam. Kemudian, memberi tugas kepada siswa secara perorangan, memberi pujian (apresiasi) kepada siswa yang menjawab pertanyaan dengan benar, dan memberikan nilai pada setiap latihan pembelajaran pendidikan agama Islam. Kendala yang dihadapi guru adalah ketidaksiapan siswa dalam menerima materi pelajaran, dan terdapat beberapa siswa yang kurang memperhatikan materi pembelajaran saat guru menjelaskan materi, serta ada juga yang tidur saat pembelajaran berlangsung. Upaya yang dilakukan oleh guru dalam menanggulangi permasalahan tersebut adalah dengan mengaktifkan suasana kelas melalui pemberian tugas serta pertanyaan langsung mengenai materi pembelajaran pendidikan agama Islam.